Predicting Financial Failure : An Empirical Investigation on Jordanian Industrial and Service Companies - Almansour, Bashar Yaser Mansour (2009)
From year to year, strong attention has been paid to the study of the problems of predicting firms’ bankruptcy. Bankruptcy prediction is an essential issue in finance especially in emerging economics. Predicting future financial situations of individual corporate entities is even more significant. Regression analysis is used to develop a prediction model on 22 bankrupt and non-bankrupt Jordanian public listed companies for the period 2000 until 2003. The results show that working capital to total assets, current asset to current liabilities, market value of equity to book value of debt, retained earnings to total asset, and sales to total asset are significant and good indicators of the probability of bankruptcy in Jordan.